Visceral crisis in metastatic breast cancer: an old concept with new perspectives - Andrade, Matheus de Oliveira (2024)
Visceral Crisis (VC) in breast cancer is a critical scenario when the burden of metastatic disease results in rapid deterioration of organ functions. There are no widely accepted objective clinical criteria for the definition of VC, and different studies have reported diverse clinical conditions such as visceral crises. Diagnosis of VC is associated with a dismal prognosis and the management of this condition is currently based on limited retrospective evidence and expert opinions. International guidelines have recommended cytotoxic polychemotherapy in the management of VC, to achieve rapid symptomatic control and preserve organ function. Nevertheless, in the case of hormone receptor-positive breast cancer, the role of chemotherapy as the treatment of choice for VC has been recently questioned, since endocrine therapy plus CDK4/6 inhibitors yielded similar response rates, with better quality of life. For HER2-positive and triple-negative breast cancer, combined chemotherapy (plus HER2-directed therapy for HER2-positive) remains a standard option for VC, but novel effective drugs such as antibody-drug conjugates are emerging and their role in the VC context shall soon be elucidated. This review aims to critically discuss the definition, prognosis, management, and future directions regarding the visceral crisis in metastatic breast cancer.